FEEDING EFFICIENCY OF CHRYSOPERLA CARNEA AGAINST APHIDS (L. ERYSIMI AND B. BRASSICAE) - RITA GUPTA; M. MOHAN (The Bioscan, 2012)
Feeding efficiency of Chrysoperla carnea against aphids was studied in the laboratory. The larvae of C. carnea are fed individually in glass vial with different sps. of aphids .The known number of aphids were provided daily in the morning hours and their number increased accordingly. Predatory efficiency was calculated by counting the numbers of aphids consumed/day. The data indicated that mean percent feeding per day by first, second and third instars larvae was 6.5, 21 and 45 on mustard aphid and 4, 24 and 35.5 on cabbage aphid. Whereas total numbers of aphids consumed by 1st, 2nd and 3rd larval instar was 6, 72.5 and100 in case of mustard aphids and 17.5, 37.5 and 71.5 in case of cabbage aphids. The 3rd instar larvae are more voracious eater of aphids in both the cases. Mean of total number of aphids consumed by respective larval instar was 178.5 and126.5 for mustard and cabbage aphids. There was a significant difference between instars efficiency when offered different hosts.